Preventive health counselling during antenatal care using the pregnancy risk assessment monitoring system (PRAMS) in Ireland - Marion Murphy; Sheena McHugh; Linda M. O'Keeffe; Richard A. Greene; Paul Corcoran; Patricia M. Kearney (BMC, 2020)
Abstract Background Maternal behaviours during pregnancy have short- and long-term consequences for maternal and infant health. Pregnancy is an ideal opportunity to encourage positive behaviour change. Despite this, limited information exists about the nature and content of lifestyle advice provided by healthcare professionals during antenatal care. Pregnancy Risk Assessment Monitoring System (PRAMS) Ireland is based on the Centers for Disease Control and Prevention (CDC) developed PRAMS that monitors maternal behaviours and experiences before, during and after pregnancy. The aim of the study was to assess the prevalence of preventive health counselling during pregnancy. Methods Secondary data analysis of the PRAMS Ireland study. Using hospital discharge records, a sampling frame of 2424 mother-infant pairs was used to alternately sample 1212 women whom had recently given birth. Preventive health counselling was defined as advice during antenatal care on smoking, alcohol, infant feeding and weight gain. Self-reported maternal behaviours (smoking/alcohol cessation, gestational weight gain, infant feeding). Univariate and multivariable analyses were conducted, adjusting for maternal characteristics. Results Among 718 women (61% response rate), the reported counselling rates were 84.8% for breastfeeding (n = 592), 48.4% for alcohol (n = 338), 47.6% for smoking (n = 333) and 31.5% for weight gain (n = 218). Women who smoked pre-pregnancy (23.7%, n = 170) were more likely to receive counselling on its effects compared to non-smokers (Adjusted Odds Ratio (AOR) 2.72 (95% Confidence Interval (CI), 1.84-4.02)). In contrast, women who did not breastfeed (AOR 0.74, 95%CI 0.44-1.26) and those who reported alcohol consumption pre-pregnancy (AOR 0.94, 95%CI 0.64-1.37) were not more likely to receive counselling on these topics. Conclusion Pregnancy is an ideal opportunity to encourage positive behaviour change. Preventive health counselling during pregnancy is not routinely provided and rates vary widely depending on the health behaviour. This study suggests that additional strategies are needed to promote positive behaviour before and during the unique opportunity provided by pregnancy.